Image Color Segmentation With Kdtree Library For Car Color Identity Classification - Joni; Erwin (International Journal of Computer Sciences and Engineering, 2021)
Joni and Erwin, Abstract, Artificial Intelligence (AI) has been widely used in analyzing objects, such as text, image, etc. There are many things that can be analyzed from images for the needs of identifying and classifying objects into certain types. One of the identifiable data is color. To identify the main color of an object, a vehicle image (car) requires a very complex analysis process. In this study, the identification process was carried out using an image center area analysis approach. This is based on the perception that the main color is in the middle of the object area. All color pixels in the analyzed area are converted to color names using the KDTree library. The segmentation process will produce several groups of color values. From the color matrix that has been through the segmentation process, the color identity of the object is obtained, which is determined by the mode value of the color matrix